IDEA STEREOTYPES IN AND OF IMAGES OF SLOVAKIA IN THE CZECH POETRY OF 1860–1939 - Tureček, Dalibor (Porównania, 2018)
The study is focused on the images of Slovakia in the Czech poetry of 1860–1939, that is the idea stereotypes that had been shaped even before the rise of a common Czech-Slovak country in 1918. At that time Slovakia was perceived in a romantic way as a land with primeval nature and people untouched by the depravity of civilization. The Slovakian pursuit of linguistic and national independence was frowned upon; the historical, ethnic and political context was overlooked and Slovakia was viewed as an integral part of the Czech national project. The Czech superior “older brother” attitude towards the Slovaks may be hyperbolically assessed as colonial.